CHEMOPREVENTIVE EFFICACY OF ADHATODA VASICA LEAVES IN 7,12- DIMETHYLBENZ[A]ANTHRACENE INDUCED ORAL CARCINOGENESIS - S. MANOHARAN; M. MANOJ PRABHAKAR (International Journal of Pharma and Bio Sciences, 2015)
Imbalance in oxidant and antioxidant status is one of the commonly observed phenomenon in several pathological conditions including cancer. Also, defect in detoxification cascade leads to accumulation of toxic metabolites, which cause mutation in DNA and leads to neoplastic transformation. Aim of the present study is to focus the chemopreventive potential of Adhatoda vasica leaves during DMBA induced hamster buccal pouch carcinogenesis by analyzing the status of lipid peroxidation by products (TBARS), antioxidants (Superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and Vitamin E) and detoxification agents (cytochrome p450, cytochrome b5, glutathione-s-transferase (GST), reduced glutathione (GSH), glutathione reductase (GR), DT-diaphorase and oxidized glutathione (GSSG)). Topical application of DMBA to the buccal pouches of hamsters, thrice a week for 14 weeks, developed well differentiated squamous cell carcinoma. At the end of the experimental period, we noticed an imbalance in oxidant and antioxidant status as well as defect in the detoxification mechanism in hamsters treated with DMBA alone. Though oral administration of ethanolic extract of Adhatoda vasica leaves (AVELet) to hamsters treated with DMBA, suppressed the tumor formation, we noticed hyperplasia and dysplasia. AVELet also modulated the status of lipid peroxidation, antioxidants and detoxification cascade in favour of delaying the tumor formation in hamsters treated with DMBA. The present study thus highlights the tumor preventive potential of AVELet, which could be attributed to its antioxidant potential during DMBA induced oral carcinogenesis. Further studies are in progress to isolate and characterize the bioactive principles from the leaves of Adhatoda vasica.